Identity Politics and Digital Branding of Political Figures on Social Media: a Case Study of President Prabowo Subianto on Tiktok in the 2024 Presidential Election - Agustina, Marlina; Dani, Muhammad Husaini (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
The 2024 Indonesian presidential election marked a significant shift in digital political communication strategies, with TikTok emerging as a central platform for shaping political identity. This study analyzes the political rebranding of Prabowo Subianto through digital public participation on TikTok constructed beyond the control of official accounts or institutional campaign narratives. Employing a descriptive-qualitative approach and constructivist paradigm, this research examines more than 150 TikTok videos uploaded between October 2023 and February 2024. Findings reveal that Prabowo’s political identity was constructed collectively through visual symbols, emotional narratives, and popular cultural expressions. Three dominant dimensions emerged: nationalism, religiosity, and emotional populism represented through viral “Prabowo Gemoy” content. TikTok operates not merely as a communication channel, but as a participatory and affective space for political meaning-making. This study asserts that effective political communication in the digital era relies not on formal narratives, but on emotional resonance and the ability to engage within a collaborative, visually driven culture.